Cloud Communities: The Dawn of Global Citizenship? - Liav Orgad (Debating transformations of national citizenship, 2018)
This kickoff contribution argues that new conceptions of global citizenship are needed today and that new digital technologies might make them viable. Blockchain technology could provide, first, every person with a unique and internationally recognized and self-sovereign legal persona that could also serve to provide individuals globally with an equal voice in international affairs. Second, blockchain technology also permits individuals or international organisations to form cloud communities in cyberspace whose aim is political decision-making and in which individuals take part in a process of governance and the creation of law.
Keywords: 330